A blaze of glory [large type] : a novel of the Battle of Shiloh - Shaara, Jeff, 1952- (Random House Large Print, 2012)
It's the spring of 1862. The Confederate Army in the West teeters on the brink of collapse following the catastrophic loss of Fort Donelson. Commanding general Albert Sidney Johnston is forced to pull up stakes, abandon the critical city of Nashville, and rally his troops in defense of the Memphis and Charleston Railroad. Hot on Johnston's trail are two of the Union's best generals: the relentless Ulysses Grant, fresh off his career-making victory at Fort Donelson, and Don Carlos Buell. If their combined forces can crush Johnston's army and capture the railroad, the war in the West likely will be over. There's just one problem: Johnston knows of the Union plans, and is poised to launch an audacious surprise attack on Grant's encampment, a small settlement in southwestern Tennessee anchored by a humble church named Shiloh.